Searching High And Low For Focus In Ibibio - Duncan, Philip; MAJOR, TRAVIS; Udoinyang, Mfon (My University, 2018)
This paper discusses two strategies in Ibibio for focusing verbs: contrastive verb focus and exhaustive verb focus. We demonstrate how these constructions differ crucially in the syntactic configurations and derivations that underlie each. Exhaustive verb focus is marked by the presence of the focus operator kpɔ́t ’only’, which is base-generated high in the left periphery and triggers phrasal movement of the TP containing the focused verb via piedpiping. Contrastive verb focus is marked by verb doubling produced by head movement, and it invokes a low focus phrase situated in the middle field, somewhere at the boundary of the inflectional and verbal domains. Both types of verb focus in Ibibio are thus syntacticallydriven, but the locus of each is split across the clausal spine, and each Foc head can probe independent of the other. Ibibio thus furnishes further evidence that multiple foci can occur in a single clause, and it also provides independent support for the existence of a low focus phrase.
Keywords: Ibibio; exhaustive verb focus; contrastive verb focus